PENGGUNAAN MIDAZOLAM INTRAVENA SECARA INTRANASAL DALAM TATALAKSANA BANGKITAN PADA ANAK - Prastiya Indra Gunawan,* Lasmauli Situmorang,* Desy Nurrosalia,* Dian Pratamastuti,* Darto Saharso* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION PROLONGED SEIZURES IN CHILDREN IS A FRIGHTENING EXPERIENCE FOR FAMILIES CESSATION OF SEIZURE AS SOON AS POSSIBLE AND EASY TO DO ARE NEEDED BECAUSE SEIZURES IN CHILDREN MOSTLY OCCUR OUTSIDE OF THE HOSPITAL BENZODIAZEPINES ARE STILL THE PRIMARY CHOICE OF TREATMENT OF SEIZURES IN CHILDREN MIDAZOLAM IS A BENZODIAZEPINE THAT EASILY TO FIND IN FORM OF INTRAVENOUS OTHERWISE IT COULD BE INITIATED INTRANASALLY